LOW ADHERENCE TO TREATMENT - A PROBLEM IN THE MANAGEMENT AND CONTROL OF BRONCHIAL ASTHMA - Keunimjay Mambetniyazov, (Central Asian Journal of Medicine, 2025)
In order to study the adherence to treatment of patients with bronchial asthma (BA), a questionnairefor the quantitative assessment of adherence to treatment (COP 25) was used, which made it possible to evaluate the indicators of "importance" and "readiness" for the componentsof "drug therapy", "medical support" and "lifestyle modification", which in patients with BA turned out to below, ranging from 42% to 68% of the maximum possible level. According to the results of our own study, the level of adherence to drug therapy in 100% of BA patients is low, amounting to only 20.9%, which means that patients will not or most likely will not follow medical recommendations and actions based on them. The level of adherence to medical support in 24% of patients with asthma had an average level (above 50%, but less than 75%), which determined that medical recommendations and actions based on them would be carried out by patients more likely than not, and 76% of patients had a low level commitment to medical support. The level of adherence to lifestyle modification in 4% of patients had an average level and in 96% - a low level. The indicator of integral adherence to treatment in 100% of patients had a low adherence level of less than 50%, amounting to only 29%, characterizing that medical recommendations and actions based on them will not be followed by patients or most likely will not be. Comparative characteristics of the factors that determine the low level of adherence of asthma patients to medical treatmentprograms, medical support and lifestyle modification do not provide statistically significant differences in study cohort groups with non-modifiable barriers, including gender, age, education, social status, disease duration and severity obstructive disorders. Increasing adherence to treatment provides a higher patient-oriented efficiency in the provision of medical care to patients, which will contribute to improving the quality and life expectancy of patients and to a large extent determine the outcome oftherapy and control of a chronic disease.